2017
DOI: 10.1371/journal.pone.0181610
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and aggressive responses to competition are moderated by contest outcome, gender, individual versus team competition, and implicit motives

Abstract: This study examined hormonal responses to competition in relation to gender, social context, and implicit motives. Participants (N = 326) were randomly assigned to win or lose in a 10-round, virtual face-to-face competition, in same-sex individual- and team-competition contexts. Saliva samples, taken before and twice after the competition, were assayed for testosterone (T), estradiol (E), progesterone (P), and cortisol (C). Implicit needs for power (nPower) and affiliation (nAffiliation) were assessed with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…However, better 177 contenders can rely on their skill, whereas less successful ones may use aggression to hamper rivals' 178 progress [9,10]. Moreover, the frustration and loss of control entailed in being repeatedly defeated should 179 facilitate rather than suppress aggression in low-status contestants [7,8,31]. In a correlational analysis and 180 two laboratory experiments we found that low competitive status, measured as competitors' relative rank 181 in a hierarchy, was linked with more frequent and intense aggressive behavior.…”
Section: Discussion 176mentioning
confidence: 99%
See 1 more Smart Citation
“…However, better 177 contenders can rely on their skill, whereas less successful ones may use aggression to hamper rivals' 178 progress [9,10]. Moreover, the frustration and loss of control entailed in being repeatedly defeated should 179 facilitate rather than suppress aggression in low-status contestants [7,8,31]. In a correlational analysis and 180 two laboratory experiments we found that low competitive status, measured as competitors' relative rank 181 in a hierarchy, was linked with more frequent and intense aggressive behavior.…”
Section: Discussion 176mentioning
confidence: 99%
“…Winners are often taken to be aggressive, not only in sportive environments [1,2] but in society at 2 large [3][4][5][6]. Contradicting this widely held assumption, the lower sense of control and the frustration 3 occasioned by frequent defeats is likely to fuel aggression in subordinate competitors [7,8]. Furthermore, 4 accomplished contestants can rely on their ability, whereas less proficient ones might compete more 5 aggressively to outweigh the skill differential.…”
Section: Introductionmentioning
confidence: 99%
“…Unhealthy chronic marital relations are often accompanied by endocrine changes, which can interfere with cardiovascular functions and the immune system (16). Concerning psychological health, chronic marital stress can lead to increased aggressiveness due to endocrine changes such as an elevation in the cortisol levels (17). Anger and hostility are factors related to marital conflict, which are often accompanied by hypertension and exaggerated physiological reactions such as variances in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…These same patterns have also been demonstrated among women, with testosterone levels increasing in anticipation of competitive matches and remaining elevated throughout the event (Bateup, Booth, Shirtcliff, & Granger, 2002; Edwards & Kurlander, 2010; Edwards, Wetzel, & Wyner, 2006; Jiménez, Aguilar, & Alvero‐Cruz, 2012); although hormone changes appeared to be less clearly related to victory or loss (Bateup et al, 2002; Edwards et al, 2006; Jiménez et al, 2012). However, hormonal responses before, during, and following competition may vary by situation (eg, win vs loss) and individual motivation (eg, affiliation with others) (Casto & Edwards, 2016a; Oxford, Tiedtke, Ossmann, Özbe, & Schultheiss, 2017). Additionally, this research has largely been limited to high‐income populations and studies in lower‐income groups have documented different patterns, such as larger spikes in testosterone levels following physically demanding horticultural activities (ie, tree cutting) in comparison to a competitive event like soccer (Trumble et al, 2013).…”
Section: Analysis Difficulties: Accounting For Variation Across Timesmentioning
confidence: 99%